OC29 Respiratory syncytial virus hospital admission and outcome in ireland among infants born less than 32 weeks gestation in the era of changing palivizumab prescription guidelines. (June 2019) - McCarthy, Karen; Moore, Eilis; Butler, Karina; Leahy, Ronan; Gavin, Patrick
Abstract : Background: Mortality and morbidity among children with Respiratory Syncytial Virus (RSV) bronchiolitis is higher among infants born prematurely and those with chronic lung or congenital heart disease. Palivizumab is a monoclonal antibody that provides passive immunity to RSV and can modify the disease course in high-risk infants. In 2006, the American Academy of Paediatrics published a clinical practice guideline recommending that infants born less than 32-weeks gestation receive Palivizumab if aged less than twelve months at the start of the RSV season. An updated guideline in 2014 however, advised that only infants less than 29-weeks should receive Palivizumab in the absence of other indications. The aim of this study was to determine the impact of changing guidelines on RSV-related hospital admissions, management and outcome among infants born <32 weeks in Ireland. Methods: Data was collected prospectively for all patients admitted with RSV bronchiolitis from 2004–2017 at a tertiary paediatric hospital. The two groups of interest were infants born <32 weeks gestation admitted from 2004–2014 and from 2014–2018. Data included demographic variables, background, management and outcome. Categorical variables were analysed using Chi-squared test. Continuous variables were analysed using Mann-Whitney test. Results: There were 2851 admissions with RSV-bronchiolitis during the study period. There were 39 infants <32 weeks admitted from 2004–2014 (2.4% total) and 28 from 2014–2018 (2.3%). Compliance with Palivizumab prescription guidelines was 53.8% pre-2014 and 78.5% post-2014 among hospitatilised infants. The proportion of paediatric intensive care unit (PICU) admissions in infants born <32 weeks gestation reduced by 20.7% and there was a 36% reduction in the requirement for mechanical ventilation in the post-2014 cohort (p 0.002). Among infants born 29–32 there were fewer PICU admissions, less ventilator support required (p=0.007) and more humidified high flow nasal cannula oxygen therapy (HHFNC) used (p 0.005). The use of nebuised saline and salbutamol significantly reduced (p0.01). The median length of hospital admission was reduced by 6 days (0.015). Conclusion: The 2014 updated AAP-guidelines on Palivizumab use has been associated with reduced prescription in the 29–32 week gestation group. This change has not resulted in increased frequency of hospital admission or PICU admission among infants <32 weeks gestation. In fact, PICU admissions reduced and the need for mechanical ventilation was significantly less. Furthermore, we have seen an improved evidence-based medicine approach to the management of these infants and a 50% reduction in median length of hospital stay.